Perancangan Teknik Motion Graphic Sebagai Media Informasi Diskominfo Kota Palembang Metode R&D Motion Graphic Engineering Design As An Information Media Diskominfo Palembang City R&D Method - Pasaribu, Dippu Rokaya; az, Azwardi; Ami, Hidayati (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
In the era of information technology, the existence of mass media is considered very important to meet the information needs of society. Many media can be used to link information. The existence of the internet also has an important meaning in changing people's habits in collecting information. Therefore, the development of the world of computers in the field of multimedia plays an important role in providing information to the public. There are so many things in the delivery of information that are processed in multimedia so that the delivery looks more understandable. Based on this, the author created a Motion Graphic Video Information Engineering Design for the Palembang City Communication and Information Service R&D method for making letters digitally with the Sidemang Application. This study uses the Research and Development method with the PPE (Planning, Production, and Evaluation) model. The author conducted tests on respondents from the Palembang City Community, 25 respondents and 2 media experts. The test results prove that the Motion Graphic Video Information Engineering Design of the Palembang City Communication and Information Service The R&D method is effective and efficient with an answer score of 71-75% in the